Optimalisasi Pemahaman Materi Cerpen Melalui Media Wordwall Pada Siswa Kelas XI SMA Islam Az Zahrah Palembang - Sefti Ninis Ariska; Emawati Emawati (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Effective learning requires creative and interactive approaches to enhance students' understanding of the material. This study focuses on evaluating the use of Wordwall as a learning tool for short stories in grade 11 at SMA Islam Az-Zahrah Palembang. The main focus of learning includes the definition, characteristics, and types of short stories. Through the "Open Box" and "Random Card" features in Wordwall, students are actively engaged in answering questions presented interactively. 1 The research method involved the delivery of material, interactive quizzes, and evaluation through pre-tests and post-tests. The results showed that the use of Wordwall significantly increased students' interest, engagement, and understanding of short story material. Thus, Wordwall has proven to be an effective and innovative learning medium in improving the quality of learning in the digital age.